1006 Impact of The Human Factor on Student Interest in Orthopaedic Surgery: A Randomised Control Trial. (12th October 2021) - Feeley, A; Feeley, I; Lee, M; Merghani, K; Sheehan, E
Abstract: Aim: The positive learning experiences of students on surgical rotations which subsequently influence career choice may be delineated into practical and interpersonal themed factors. It remains unclear the relative impact each component has on the student experience and subsequent specialisation. We evaluated the influence of having senior resident mentor during practical simulation in orthopaedic surgery has on medical student interest in surgery; their comfort in theatre; and its role in enhancing knowledge acquisition within the rotation Method: Medical students undergoing clinical rotations in a Regional University Hospital were randomised to undertaking a a virtual reality simulated operation independently or performing under the guidance of an experienced resident. Baseline levels of interest in surgery, comfort in theatre, perceived barriers to surgical learning and entry to surgery were established and compared to answers following completion of the tutorial. Qualitative feedback was collected regarding the benefits and limitations to the experience. Presented according to CONSORT guidelines. Results: Participants in the resident guided group achieved significantly higher simulated performance scores compared to the control (p < 0001), with an increase in orthopaedic surgery from baseline expressed to a statistically significant degree (p = 0.04). 100% participants strongly agreed it was a beneficial learning experience which would be useful in surgical curricula. Conclusions: Surgical trainee guided simulation led to improved performance and interest in orthopaedic surgery, while virtual practical experience was felt to be a useful learning tool independent of supervision. Further research is needed to establish the role of interpersonal interactions in student surgical experience.